Collaboration of indigenous African and Western European medicine : policy guidelines. - Jali, Martha Nozizwe (My University, 2009)
The primary aim of this study was to advocate for a collaborated health care delivery system that includes indigenous African medicine and is administered and controlled by the government. The objectives were:  To demonstrate how apartheid disrupted the natural development of indigenous healing practices. To dispel the misconception about the use of indigenous African medicine in the treatment of diseases. To demonstrate the need to protect both indigenous African and western European medicine. To demonstrate that African patients consult both indigenous African and western European doctors for various aspects of their treatment in their health care choices. To demonstrate that patients expect the government to provide an effective health delivery system. The main research question was: How can South Africa develop a collaborated health care delivery system using both indigenous African and biomedical health professionals that is effective and open to everyone on an equal basis? The theoretical framework for this study was the Afro-centric worldview in which events and ideas are perceived from an African perspective with the African people as the main players rather than victims. At the centre of the study were the African people, their health, disease pattern and healing practices. The Afro-centric qualitative research design was used. A sample size of 15 indigenous African doctors, 50 western European oriented health professionals and 84 patients participated in the study. The open coding method of data analysis was used to analyze data obtained from semi-structured in-depth interviews. The major findings of the study are that:  The belief of the African people in the existence of the ancestors and spirituality remains unshakeable. The strong belief n the ancestors make the diagnosis and treatment of diseases essentially religious practices. In the African culture, there are no preventative measures against natural illnesses, but there are preventative measures that are used against witchcraft/sorcery from entering a homestead and causing illness among members of a family. African people utilize both health care systems simultaneously and/or interchangeably depending on the seriousness of the illness and the knowledge and experiences that the illness can be effectively treated using indigenous African medicine or biomedicine. Both indigenous African doctors and biomedical health professionals play an important role in the provision of health. Recommendations The study recommends that when policy guidelines on the collaboration of indigenous African and western European medicine are drawn up, the following should be considered: Legislation to protect indigenous knowledge on African medicine Legislation that controls the qualification and registration of indigenous African doctors. Inclusion of indigenous African medicine in the curricula of all health professionals.
Thesis (Ph.D.)(Political Science) --University of Limpopo, 2009.
Keywords: Indigenous Peoples; Western European Medicine; Health Policy Guidelines; Indigenous Medicine; 615.10968; Health policy; Pharmacology